Material Obstacles to Protest in the Urban Built Environment: Insights from Jordan. Issue 1 (1st June 2020) - Schwedler, Jillian
Abstract: How has the Jordanian state sought to police protests through control of material space? How have other changes to the built environment limited possibilities for protests? This article articulates the beginnings of a new typology for understanding how changes to the built environment can create obstacles to protests. I identify three distinct changes that have affected spaces of protest: (1) the spatial expansion of the city to accommodate population growth, absorb two major waves of refugees since 2003, and facilitate massive foreign investment in urban megaprojects; (2) infrastructural development, including urban sprawl, new bypass roads and overpasses, and the services necessary for the construction of megaprojects; and (3) the policing of spaces where protests had previously taken place, in part by rendering them inaccessible. I draw on archival material, elite interviews, and ethnographic observation of protests in Amman, Jordan.